Socio-ecological Model as a Framework for Overcoming Barriers and Challenges in Randomized Control Trials in Minority and Underserved Communities - Hamisu M. Salihu, MD, PhD; Ronee E. Wilson, PhD, MPH; Lindsey M. King, MPH, CHES, CCRP; Phillip J. Marty, PhD; Valerie E. Whiteman, MD (Global Health and Education Projects, Inc., 2014)
Background:  Numerous barriers and challenges can hinder the successful enrollment and retention of study participants in clinical trials targeting minority populations. To conduct quality research, it is important to investigate these challenges, determine appropriate strategies that are evidence-based and continue seeking methods of improvement. Methods:  In this paper, we report such experiences in a registered clinical trial in an underserved minority population in the Southern part of United States. This research study is a randomized doubleblind controlled clinical trial that tests the efficacy of higher-strength as compared to low-strength/standard of care folic acid to prevent fetal body and brain size reduction in pregnant women who smoke.  A unique approach in this socio-behavioral, genetic-epigenetic clinical trial is that we have adopted the socio-ecological model as a functional platform to effectively achieve and maintain high participant recruitment and retention rates. Results:  We highlight the barriers we have encountered in our trial and describe how we have successfully applied the socio-ecological model to overcome these obstacles. Conclusions and Global Health Implications:  Our positive experience will be of utility to other researchers globally. Our findings have far-reaching implications as the socio-ecological model approach is adaptable to developed and developing regions and has the potential to increase recruitment and retention of hard-to-reach populations who are typically under-represented in clinical trials. Key words: Participant Enrollment • Recruitment • Genetic-Epigenetics • Socio-Ecological Model (SEM) • Clinical Trials • Retention • Challenges Copyright © 2015 Salihu et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.